Multiple‐input multiple‐output symbol rate signal digital predistorter for non‐linear multi‐carrier satellite channels. Issue 16 (1st November 2015) - Zenteno, Efrain; Piazza, Roberto; Bhavani Shankar, M.R.; Rönnow, Daniel; Ottersten, Björn
Abstract : A digital predistortion (DPD) scheme is presented for non‐linear distortion mitigation in multi‐carrier satellite communication channels. The proposed DPD has a multiple‐input multiple‐output architecture similar to data DPD schemes. However, it enhances the mitigation performance of data DPDs using a multi‐rate processing algorithm to achieve spectrum broadening of non‐linear operators. Compared to single carrier (single‐input single‐output) signal (waveform) DPD schemes, the proposed DPD has lower digital processing rate reducing the required hardware cost of the predistorter. The proposed DPD outperforms, in total degradation, both data and signal DPD schemes. Further, it performs closest to a channel bound described by an ideally mitigated channel with limited maximum output power.